Seleção recorrente visando à tolerância para a murcha bacteriana em tabaco - Silva, Reberth Renato da (2019)
Bacterial wilt whose causal agent is Ralstonia solanacearum is one of the most economically important diseases for tobacco cultivation (Nicotiana tabacum L.) worldwide. It causes the atrophy and yellowing of the leaf tissues from the youngest leaves and can evolve throughout the plant. As chemical control is of reduced efficiency the only viable alternative is the selection of resistant lines/hybrids. As the genetic control of the pathogen is apparently polygenic, the main strategy for success is the use of recurrent selection (RS). To achieve this objective, the RS population of the Souza Cruz company, of the Virginia varietal group, was used to verify the viability of use this breeding strategy aiming at tolerance to R. solanacearum. Additionally, to verify which type of progeny is most viable for the conduction of RS and to estimate a possible association between the number of plants with symptoms (NPWS) and the agronomic performance of tobacco. For this, some experiments were conducted under field conditions. In the 2017/18 season, 100 S 1:2 progenies from the original population (C0) and 108 of the cycle I (CI) half sib progenies were evaluated. In the following season, 196 S 0:1 progenies of the CI and 176 progenies of the CII were evaluated. The experiments were conducted in an area with a historic of pathogen occurrence in Canoinhas (SC). To ensure the occurrence of the pathogen, at 40 to 45 days after transplanting of the seedlings were inoculated the bacteria. The incidence of the pathogen was evaluated by the number of plants with symptoms. In the 2017/18 season, the productive potential of the plants was also visually evaluated. It was found that the heterogeneity of pathogen distribution in the area contributed to the low experimental accuracy. In this condition the genetic variation was, regardless of the type of progeny used, of small magnitude. However, even in this scenario the difference in tolerance between progenies was associated with agronomic performance and recurrent selection showed that it was slightly efficient in the accumulation of favorable alleles aiming at greater tolerance to the pathogen. New phenotyping strategies of the progenies should be sought to obtain safer information in relation to tolerance to R. solanacearum.